2019
DOI: 10.1115/1.4043644
|View full text |Cite
|
Sign up to set email alerts
|

Stall Inception in a Boundary Layer Ingesting Fan

Abstract: Jet engines with boundary layer ingestion (BLI) could offer significant reductions in aircraft fuel burn compared with podded turbofans. However, the engine fans must run continuously with severe inlet distortion, which is known to reduce stability. In this paper, an experimental study has been completed on a low-speed rig fan operating with a BLI-type inlet distortion. Unsteady casing static pressure measurements have been made at multiple locations during stall events. Steady-state, full-annulus area travers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…FIGURE 10). Besides, this definition is very conservative as it implies that a blade only needs to reach stall conditions at a specific circumferential location for the entire row to be considered in stall conditions, which has been demonstrated not to be always the case [13].…”
Section: Conclusion Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…FIGURE 10). Besides, this definition is very conservative as it implies that a blade only needs to reach stall conditions at a specific circumferential location for the entire row to be considered in stall conditions, which has been demonstrated not to be always the case [13].…”
Section: Conclusion Discussion and Perspectivesmentioning
confidence: 99%
“…It is therefore important to take them effectively and efficiently into account, even during the first steps of the design. The impact of inlet distortion has been assessed in many studies [11,12,13]. They have in particular emphasized the importance of not only stagnation pressure [14] but also swirl distortion to account for performance and stability margin losses and have proposed relevant metrics to assess these distortions [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental rig and test case used in this paper is the low-speed, single-stage fan rig shown in Figure 3 and described in [1,7]. The rig was purpose-built for measuring fan-distortion interaction, with a long intake duct that allows the rotor to interact freely with the distorted upstream flow field.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, both the stalls of rotors were caused by the spike disturbances finally. Perovic et al [3] showed that the spike disturbance is generated near the tip region and develops into the rotating cell. Therefore, it was considered that the Sweep caused some change in the flow field near the tip region at a low flow rate.…”
Section: Discrete Spatial Fourier Series (Dsfs) Analysismentioning
confidence: 99%
“…BLI engines intake the boundary layer flow of aircraft and operate at the distorted inflow condition. The experimental study using the fan with the distortion gauze to generate the inlet distortion of BLI profile has been conducted by Perovic et al [3]. It is revealed that the disturbance occurs in the region of the low-momentum fluid and the stall inception with the inlet distortion is initiated by this disturbance when it grows and propagates around the entire annulus.…”
Section: Introductionmentioning
confidence: 99%